2023
DOI: 10.1071/wr23026
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of morphometrics and body condition between two breeding populations of Australian humpback whales

Grace Russell,
Fredrik Christiansen,
Andrew Colefax
et al.

Abstract: Context The east and west coasts of Australia form the breeding grounds for two of the world’s largest and fastest-growing populations of humpback whales (Megaptera novaeangliae). These populations show differences in mean lipid content, fatty acid profiles, and stable isotope values. Aims To determine whether these differences result in variation in nutritional health and physiology between populations, we quantified and compared the morphology, body condition and energetic requirements between the tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 81 publications
(142 reference statements)
0
1
0
Order By: Relevance
“…Comparative studies of body condition in Australian humpbacks have found that adults, particularly lactating females from the west coast population have poorer body condition than their east coast counter parts, with potential links to environmental drivers such as the El Nino Southern Oscillation, Southern Antarctic Mode and Indian Ocean Dipole(Russell et al 2023). While humpback whales in Australia are considered to be recovered and are no longer listed as threatened within Australia (Threatened Species Scienti c Committee 2022), they remain protected as a migratory cetacean species under the EPBC Act.…”
mentioning
confidence: 99%
“…Comparative studies of body condition in Australian humpbacks have found that adults, particularly lactating females from the west coast population have poorer body condition than their east coast counter parts, with potential links to environmental drivers such as the El Nino Southern Oscillation, Southern Antarctic Mode and Indian Ocean Dipole(Russell et al 2023). While humpback whales in Australia are considered to be recovered and are no longer listed as threatened within Australia (Threatened Species Scienti c Committee 2022), they remain protected as a migratory cetacean species under the EPBC Act.…”
mentioning
confidence: 99%